“The Problem of the Adjective” - Jessica Feldman (Transposition)
The realm of the voice and the realm of the affective often share the distinction of the ineffable. Over the past 5-10 years, there has been a proliferation of scientific research and commercial products focused on the measurement of affect in the voice, attempting to codify and quantify that which previously had been understood as beyond language. Following similar work regarding the digital detection of facial expressions of emotion, this form of signal capture monitors data “below the surface,” deriving information about the subject’s intentions, objectives, or emotions by monitoring the voice signal for parameters such as timing, volume, pitch changes, and timbral fluctuation. Products claim to detect the mood, personality, truthfulness, confidence, mental health, and investability quotient of a speaker, based on the acoustic component of their voice. This software is being used in a range of applications, from targeted surveillance, mental health diagnoses, and benefits administration to credit management. A study of code, schematics, and patents reveals how this software imagines human subjectivity, and how such recognition is molded by, and in service of, the risk economy; revealing an evolution from truth-telling, to diagnostic, to predictive forms of listening.